2020
DOI: 10.18632/aging.103812
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2 correlates with tumor immune infiltrates in lower-grade glioma

Abstract: Immunotherapy is an effective treatment for many cancer types. However, YTHDF2 effects on the prognosis of different tumors and correlation with tumor immune infiltration are unclear. Here, we analyzed The Cancer Genome Atlas and Gene Expression Omnibus data obtained through various web-based platforms. The analyses showed that YTHDF2 expression and associated prognoses may depend on cancer type. High YTHDF2 expression was associated with poor overall survival in lower-grade glioma (LGG). In addition, YTHDF2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Our study found that YTHDF2 was significantly related to LGG patients' overall survival (p < 0.001). A recent study has demonstrated that YTHDF2 acts as a potential biomarker that correlated with the LGG-infiltrating immune cells (Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that YTHDF2 was significantly related to LGG patients' overall survival (p < 0.001). A recent study has demonstrated that YTHDF2 acts as a potential biomarker that correlated with the LGG-infiltrating immune cells (Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Garzon-Muvdi et al, 2018, have supported the prominence of DC activation in enhancing the efficacy of anti-PD-1 immunotherapy against glioblastoma [ 16 ]. Taken together, this study reveals the importance of targeting YTHDF2 in combination with DC-immunotherapy [ 7 ] to enhance the efficacy of ICB therapy against early stage brain tumors [ 15 ], ( Table 3 ).…”
Section: Epitranscriptomics In Icb-therapeuticsmentioning
confidence: 91%
“…Lin et al, 2020 [ 15 ] demonstrated the role of YTHDF2 in progression of lower-grade glioma (LGG) also called ‘pilocytic astrocytoma’, a type of early stage brain tumor. They showed that YTHDF2 is abnormally expressed in various types of cancers and reduces overall longevity and survival.…”
Section: Epitranscriptomics In Icb-therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher expression of YTHDF2 has been positively correlated with immune cell (B-cells, T-cells, DCs, MΦ and neutrophils) expressing PD-1, TIM-3 and CTLA-4 markers. Therefore, targeting YTHDF2 in DCs would hold the potential to enhance anti-tumor immunity in combination with ICB-therapeutics [74,76]. A similar pre-clinical trial was proposed by jubilant-therapeutics targeting PD-1 inhibitor (with brain penetrant PRMT5) in controlling LGG, potentiating the scope to utilize in combinations with immune cells targeting intracellular checkpoints as targeted therapy.…”
Section: Ythdf1 In Anti-pd1 Resistance (Solid Tumors)mentioning
confidence: 99%